Photo-enhanced uptake of SO2 on Icelandic volcanic dusts. Issue 3 (17th February 2022) - Lasne, Jerome; Urupina, Darya; Maters, Elena C.; Delmelle, Pierre; Romanias, Manolis N.; Thevenet, Frederic
Abstract : Laboratory study evaluating the impact of relative humidity and simulated sunlight radiation on SO2 uptake on natural volcanic particles. Abstract : Iceland is the largest volcanic dust (v-dust) desert on Earth, with an estimated area of 22 000 km 2 . In addition, Iceland is one of the most active aeolian areas in the world, with frequent high-velocity winds resuspending v-dust from the ground into the atmosphere. Suspended v-dust particles can then be transferred over thousands of kilometers, reaching as far as central Europe. Once released into the atmosphere, v-dust particles can interact or react with atmospheric pollutants. In this study, we investigate the heterogeneous reactivity of sulfur dioxide (SO2 ), one of the most prominent gases released by volcanic eruptions, with Icelandic v-dust particles, and the influence of relevant atmospheric parameters, such as relative humidity (RH) and ultraviolet (UV) light flux, on this reactivity. The experiments are conducted at atmospheric pressure in a coated-wall flow-tube reactor coupled with an SO2 analyzer. To quantify the heterogeneous processes, we determine the initial number of SO2 molecules taken up by dust, N S, and the steady-state uptake coefficient, γ ss, of SO2 on different v-dusts. N S increases with RH and with the photon flux characterized by the photolysis rate of NO2 in the setup, J NO2 . The photo-enhanced removal of SO2 is also found to depend on the surface elemental composition of v-dust particles, and an empirical parametrization of the photo-induced effect is proposed to account for the most important environmental factors, leading to the general expression: N S, light / N S, dark = 6.1 × (1 + 7.76 × 10 −2 × RH) × (1 + 480.5 × J NO2 ) × (Ti/Si). The steady-state uptake coefficients of SO2 are in the 10 −8 range, once normalized to the specific surface area of v-dust. RH and UV light influence the value of γ ss, but to a lesser extent than they influence N S . Our results suggest that the photo-induced heterogeneous uptake of SO2 on v-dust particles may provide a significant sink of sulfur in volcanic clouds, and should be taken into account in atmospheric modeling.